STATE OBLIGATIONS RELATED TO THE LAUNCH OF OBJECTS INTO OUTER SPACE UNDER INTERNATIONAL LAW - Riza Amalia (Lampung Journal of International Law, 2020)
Space utilization is currently experiencing a very rapid increase. Many countries have carried out various missions by launching space objects. In launching an object into space, the state has several obligations that must be fulfilled, at least according to the author there are three basic obligations namely, registration, supervision, and responsibility when a loss occurs. For this reason, this study aims to provide information on how to carry out these obligations under international law. The method used in this study is the normative judicial approach. A normative juridical approach is a legal research conducted by examining library materials or secondary data as a basis for research by conducting a search of regulations and literature relating to the problem under study. The launch of space objects certainly has a regulation that is used as a standard worthy of launching space objects such as satellites. The launch is regulated in the 1976 Registration Convention and registered with an international institution, the International Telecommunication Union (Article iv (1) 1976 registration convention). In addition to registering space objects, the state must also supervise these space objects to find out the development of the mission they made (Article VI Outer Spece Treaty 1967), and the last is the responsibility of a country when a loss arises due to the space object. This is regulated in the 1967 Outer Space Treaty (Article VII) and the 1972 Liability Convention.